A cross-sectional prevalence survey of psychotropic medication prescribing patterns in prisons in England - Lamiece Hassan; Martin Frisher; Jane Senior; Mary Tully; Roger Webb; David While; Jenny Shaw (National Institute for Health Research, 2014)
Background: The prevalence of mental illness is significantly higher among prisoners than among people in the wider community. Psychotropic prescribing in prisons is a complex and controversial area, where prescribers balance individual health needs against security and safety risks. However, there are no current data on prescribing patterns in prisons or how these compare with those in the wider community. Aims: The study aimed to determine the prevalence, appropriateness and acceptability of psychotropic prescribing in prisons. The objectives were to determine rates of prescribing for psychotropic medications, compared with those in the wider community; the appropriateness of psychotropic prescribing in prisons; and the perceived satisfaction and acceptability of prescribing decisions to patients and general practitioners (GPs). Method: Eleven prisons, housing 6052 men and 785 women, participated in a cross-sectional survey of psychotropic prescribing. On census days, data were extracted from clinical records for all patients in receipt of hypnotics, anxiolytics, antipsychotics, antimanics, antidepressants and central nervous system stimulants. The Clinical Practice Research Datalink supplied an equivalent data set for a random sample of 30,602 patients prescribed psychotropic medicines in the community. To determine the acceptability of prescribing decisions, patients attending GP consultations at three prisons were surveyed (n = 156). Pre- and post-consultation questionnaires were administered, covering expectations and satisfaction with outcomes, including prescribing decisions. Doctors (n = 6) completed post-consultation questionnaires to explore their perspectives on consultations. Results: Overall, 17% of men and 48% of women in prison were prescribed at least one psychotropic medicine. After adjusting for age differences, psychotropic prescribing rates were four times higher among men [prevalence ratio (PR) 4.02, 95% confidence interval (CI) 3.75 to 4.30] and six times higher among women (PR 5.95, 95% CI 5.36 to 6.61) than among community patients. There were significant preferences for certain antidepressant and antipsychotic drugs in prison, compared with in the community. In 65.3% of cases, indications for psychotropic drugs were recorded and upheld in the British National Formulary. Antipsychotic prescriptions were less likely than other psychotropics to be supported by a valid indication in the patient notes (PR 0.75, 95% CI 0.67 to 0.83). In the acceptability study, patients who identified mental health as their primary problem were more likely than individuals who identified other types of health problems to want to start, stop and/or change their medication (PR 1.46, 95% CI 1.23 to 1.74), and to report dissatisfaction following the consultation (PR 1.76, 95% CI 1.01 to 3.08). Doctors were more likely to issue prescriptions when they thought that the patient wanted a prescription (PR 4.2, 95% CI 2.41 to 7.28), they perceived pressure to prescribe (PR 1.66, 95% CI 1.26 to 2.19), and/or the problem related to mental health (PR 1.67, 95% CI 1.27 to 2.20). Conclusions: Psychotropic medicines were prescribed more frequently in prisons than in the community. Without current and robust data on comparative rates of mental illness, it is not possible to fully assess the appropriateness of psychotropic prescribing. Nonetheless, psychotropic medicines were prescribed for a wider range of clinical indications than currently recommended, with discernible differences in drug choice. Complex health and security concerns exist within prisons. Further research is necessary to determine the effect of psychotropic prescribing on physical health, and to determine the optimum balance between medicines and alternative treatments in prisons. Funding: The National Institute for Health Research Health Services and Delivery Research programme.